THE EFFECT OF EMPOWERMENT AND LEADER MEMBER EXCHANGE ON EMPLOYEE PERFORMANCE WITH SELF EFFICACY AS A MEDIATION VARIABLE - Fahmi, Khaerul (Journal of Industrial Engineering & Management Research, 2019)
This study was conducted with the aim of analyzing the effect of Empowerment on Self Efficacy, the influence of Leader Member Exchange (LMX) on Self Efficacy, the effect of Empowerment on Employee Performance, the influence of Leader Member Exchange (LMX) on Employee Performance, the influence of Self Efficacy on Employee Performance, the role of Self Efficacy as the mediating variable is the influence of Empowerment on Employee Performance and the role of Self Efficacy as a mediating variable for the effect of LMX on Employee Performance. This research was conducted using the Census method with 390 respondents from industrial employees in Tangerang. Data testing techniques in this study include validity test, reliability test, multiple regression analysis, t test, and mediation test to test and prove the hypothesis. Based on data analysis shows that Empowerment has a positive effect on Self Efficacy, Leader Member Exchange (LMX) has a positive effect on Self Efficacy, Empowerment has a positive effect on Employee Performance, Leader Member Exchange (LMX) has a positive effect on Employee Performance, Self Efficacy has a positive effect on Performance Employees, Self Efficacy is able to mediate the influence of empowerment on employee performance. And Self Efficacy is able to mediate the influence of leader member exchange (LMX) on employee performance.